miR-125a Suppresses TrxR1 Expression and Is Involved in H2O2-Induced Oxidative Stress in Endothelial Cells - Fangjie Chen; Hong Liu; Jingjing Wu; Yanyan Zhao (Journal of Immunology Research)
Thioredoxin reductase (TrxR), an antioxidant enzyme dependent on nicotinamide adenine dinucleotide phosphate, plays a vital role in defense against oxidative stress. However, the role of microRNAs targeting TrxR under oxidative stress has not yet been determined. In this study, we tested the involvement of miRNA-mediated posttranscriptional regulation in H2O2-induced TrxR1 expression in endothelial cells. Dual luciferase assay combined with expression analysis confirmed that miR-125a suppressed TrxR1 expression by targeting its 3′-UTR. Furthermore, H2O2 induced TrxR1 expression partly through downregulation of miR-125a. These findings indicate that miRNA-mediated posttranscriptional mechanism is involved in H2O2-induced TrxR1 expression in endothelial cells, suggesting an important role of miRNAs in the response to oxidative stress.